Domestic and Foreign Experience of Training Social Workers - Rebukha, Liliia (Pedagogical Discourse, 2017)
The author analyzed in the article the textbooks and scientific articles that reflect the peculiarities and importance of the development of professional social education. The attention is drawn to the fact that at the beginning of the 20th century positive conditions have developed in Ukraine for a special training of social workers and professional support of the needy. It is noted that in spite of a certain achievements in the training of specialists in the social sphere, the university education of social workers has not been formed in the former Soviet Ukraine. It has been observed that since the beginning of the last century, professional social literacy has been improved and rapidly expanded in foreign countries. The high efficiency of the social workers training system has been proved in the USA, England, France, Germany, Sweden and other European countries. Their experience is assessed for our country, because it helped to revive the university training of social workers at the end of the 20th century. The article draws attention to the fact that a multi-level system of university training of social workers is being formed in Ukraine now. This system replaced the one-stage education as a result of the coherence between the borrowed European schemes of higher education organization and the urgent need for introducing the variability of forms of education in the conditions of a constantly changing Ukrainian society. It is shown that university training in the specialty «Social work» is carried out on the bachelor’s and master’s level according to the standard of the higher education of Ukraine. It is noted that the standard defines a set of requirements for the content of the study and the results of educational activities of the higher school in order to ensure the formation of general and professional competencies of students in the given specialty. It is concluded that there was not an easy way in the development of professional training of the social workers in foreign countries and in Ukraine: from courses and schools with a lower level of education to higher university education. Proceeding from this, nowadays the main task of the higher social education of Ukraine is finding out its special, original, unmistakable path in the system of training specialists in the social sphere.